IMPLEMENTATION OF SAFETY AND SECURITY IN BUSINESS TOURISM TRANSPORTATION - Michael Yuda Delo (Politeknik Pariwisata Makassar, 2025)
This study examines safety and comfort in the tourism transportation business. The purpose of this paper is to describe safety and security in the tourism transportation business, including fleet conditions, driver behavior, and company management systems. This study also aims to formulate strategies to improve safety and security, thereby ensuring tourists feel more protected and enhancing their experience. The research method used is descriptive qualitative. Data were obtained through direct observation of tourism transportation services, interviews with management, drivers, and tourists, and the use of documents related to company operational standards and government regulations. Furthermore, a SWOT analysis was used to identify strengths, weaknesses, opportunities, and threats. The results show how safety and security are portrayed in the tourism transportation business. Safety and security issues indicate that most tourism transportation companies have made efforts to maintain safety and security, but various shortcomings remain. Identified obstacles include inconsistent fleet maintenance, uneven driver skills, and limited systems for monitoring the safety of goods and passengers. Tourists also expressed anxiety, especially during long-distance or nighttime trips. Strategies to improve safety and security are proposed. The analysis resulted in several strategic proposals, including improving regular driver training, using assistive technology such as GPS and CCTV, developing stricter and more consistent operational standards, strengthening cooperation with police and tourism agencies, and implementing safety education campaigns for tourists.